Chromosomal alterations in patients treated at an Early Diagnosis and Intervention Center in the city of Araraquara- SP (Revista Brasileira Multidisciplinar, 2026)
Chromosomal abnormalities are considered one of the biggest causes of genetic disease. These abnormalities are classified as structural chromosomal  or numerical, which may involve autosomal, sexual chromosome or both. People with chromosomal abnormalities present multisystem involvement, such alterations are responsable for hight morbidity and increased mortality at all ages therefore, it´s necessary to have a multidisciplinary approach to improve the quality of life and prevent early mortality in these patientes. Objective: To identify chromosomal abnormalities in patients referred to Centro de Diagnóstico e Intervenção Precoce (CDIP) Araraquara - SP. Methodology: A retrospective-quantitative survey was carried out of newborns diagnosed with chromosomal change referres to the CDIP in the period 1999-2015. Results: 80 patients with chromosomal change were identified, 100% of them numerical, 98,75% had abnormalities in autosomal chromosome and 1,25% in sex chromosome. Among the autosomal chromosomal abnormalities, trisomy 21 was the most prevalent, followed by trisomy 18 and trisomy 13. monosomy of the X chromosomal was the only found, involving sex chromosomal. Furthermore, it was observed that women in all age can have children with aneuploidy, especially Down Syndrome, however, mother over 35 have an increased chance of this happening. Conclusion: These results are relevant and in agreement with the literature. Furthermore, the service offered by the CDIP in te city of Araraquara- SP is of high relevance since this Center, maintained by Araraquara city hall, enable the eraly and accurate diagnosis of such changes, as wll as monitoring yhe evolution of these patientes from 0 to 3 years of age.
Keywords: Chromosomal abnormalities; Maternal age; Down´s Syndrome